From investigation to detection: Criminal Investigation Organs of Perm province during years of revolution and civil war in Russia - V. I. Teterin (Омский научный вестник: Серия "Общество. История. Современность")
Despite the high actuality of the subject connected with the necessity of building a civil society in our country the modern historiography does not cover а complex study of the soviet system of criminal investigation formation in certain regions. The present study elaborates on criminal investigation institutions in Perm region under the soviet authorities coming to power. With the help of the archive documents from the State Archive of Perm region and the Perm police history museum the author disovers some historic facts related to organization and functioning of criminal investigation in Perm region. Following the collapse of monarchy in 1917 the whole Russian law-enforcement system began to transform. New transformations took place when the Bolshevists came to power in autumn 1917. Criminal investigation was no exception. Along with that a kind of continuity was characteristic of the system despite all the political changes. A lot of investigators, some having started their career before the revolution, continued working under both the white and the red. However the revolution and the Civil War could not leave the criminal situation in the region and investigating agencies intact. Ideology affected their activity a lot. The crisis destroyed the resource base and personnel development system. But that did not prevent the authorities from achieving high crime detection and containing the chaos in the region. During the first years of the soviet power the fundament for the effective functioning of the investigation institutions was created